2021
DOI: 10.30892/gtg.35230-677
|View full text |Cite
|
Sign up to set email alerts
|

Geography of Natural and Recreational Facilities in the Development of Economic Integration of the Border Areas of Northern Kazakhstan and the Russian Federation

Abstract: This study presents the natural and recreational prerequisites for the formation and development of the cross-border tourism industry in the Kazakh-Russian border region in the context of modern integration processes. The purpose of the research is to identify the main natural and recreational resources in the border regions of Northern Kazakhstan, among which the border regions are Kostanay, Pavlodar and North Kazakhstan regions, and the constituent entities of the Russian Federation bordering on them. The sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To enhance the efficacy of longevity tourism endeavors in Bama and steer tourists toward affirmative behavioral inclinations, several measures may be instituted. Augmenting the substance of activities with indigenous attributes and longevity culture, encompassing traditional festivities, theatrical exhibitions, and the dissemination of longevity wisdom, can elevate the overall allure and interest of the activities (Sansyzbayeva et al, 2021;Demkova et al, 2022). Incorporating technological interactive elements is also recommended to infuse modernity and engagement into the experience.…”
Section: Improve Activity Effects and Guide Behavioral Intentionsmentioning
confidence: 99%
“…To enhance the efficacy of longevity tourism endeavors in Bama and steer tourists toward affirmative behavioral inclinations, several measures may be instituted. Augmenting the substance of activities with indigenous attributes and longevity culture, encompassing traditional festivities, theatrical exhibitions, and the dissemination of longevity wisdom, can elevate the overall allure and interest of the activities (Sansyzbayeva et al, 2021;Demkova et al, 2022). Incorporating technological interactive elements is also recommended to infuse modernity and engagement into the experience.…”
Section: Improve Activity Effects and Guide Behavioral Intentionsmentioning
confidence: 99%
“…For example, according to changes in the temperature regime, it was concluded that since 1850, over 166 years, the temperature has increased in South Kazakhstan by an average of 0.27 °C per decade, while over the past 30 years it has increased by 044 °C (17) . In connection with this research topic, regional scientific journals present the results on the dynamics of the glacial runoff of the rivers of the Northern slope of the Ile-Alatau and identify trends in the further evolution of glaciation this area (18) . For the prospective development of the tourism industry in the Almaty region, Goal 17 -Partnerships for the Goals is quite relevant.…”
Section: The Top Ten Areas Of Tourist Activity In the Republic Of Kaz...mentioning
confidence: 99%